The Planning Process of the Online Transaction Fraud Detection Using Backlogging on an E-Commerce Website - Atiqah Solehah Mat Taupit; Nurdiana Azizan (USIM Press, 2024)
VOL. 9 NO. 1 (2023) Page (56-62)